Facies and depositional architecture according to a jet efflux model of a late Paleozoic tidewater grounding-line system from the Itararé Group (Paraná Basin), southern Brazil. (April 2016) - Aquino, Carolina Danielski; Buso, Victoria Valdez; Faccini, Ubiratan Ferrucio; Milana, Juan Pablo; Paim, Paulo Sergio Gomes
Abstract: During the Late Paleozoic, the Gondwana supercontinent was affected by multiple glacial and deglacial episodes known as "The Late Paleozoic Ice Age" (LPIA). In Brazil, the evidence of this episode is recorded mainly by widespread glacial deposits preserved in the Paraná Basin that contain the most extensive record of glaciation (Itararé Group) in Gondwana. The Pennsylvanian to early Permian glaciogenic deposits of the Itararé Group (Paraná Basin) are widely known and cover an extensive area in southern Brazil. In the Doutor Pedrinho area (Santa Catarina state, southern Brazil), three glacial cycles of glacier advance and retreat were described. The focus of this article is to detail the base of the second glacial episodes or Sequence II. The entire sequence records a deglacial system tract that is represented by a proximal glacial grounding-line system covered by marine mudstones and shales associated with a rapid flooding of the proglacial area. This study deals with the ice proximal grounding-line systems herein interpreted according to lab model named plane-wall jet with jump. Detailed facies analysis allowed the identification of several facies ranging from boulder-rich conglomerates to fine-grained sandstones. No fine-grained deposits such as siltstone or shale were recorded. According to this model, the deposits are a product of a supercritical plane-wall outflow jet that changes to a subcritical jet downflow from a hydraulic jump. The hydraulic jump forms an important energy boundary that is indicated by an abrupt change in grain size and cut-and-fill structures that occur at the middle-fan. The sedimentary facies and facies associations show a downflow trend that can be subdivided into three distinct stages of flow development: (1) a zone of flow establishment (ZFE), (2) a zone of transition (ZFT), and (3) an established zone (ZEF). The proximal discharge is characterized by hyperconcentrated-to-concentrated flow due to the high energy and sediment-laden nature of the flows. At the transitional zone, a hydraulic jump produces a rapid shift of conglomeratic to sandy facies with associated scour features. Towards the distal zones, the jet detaches to originate a vertical turbulent jet characterized by more diluted flows. Discussion of fan facies and architecture within a framework of jet-efflux dynamics provides an improved understanding of grounding-line fans systems that produce coarse-grained strata commonly enclosed by fine-grained rocks. The results have clear implication in terms of prediction of facies tract and geometry of oil and gas reservoirs deposited under similar conditions. And also can be useful to identifying the position of a glacial terminus through time. Graphical abstract: Highlights: The evidence of the LPIA in Brazil is recorded by the Itararé Group. The facies association satisfactorily fit a subaqueous grounding-line fan model. The sedimentology could be taken according to the plane-wall jet with jump model. Hydraulic jump occurs during the passage from supercritical to subcritical flow. Hydraulic jump produces a rapid shift of facies and scours features.